Effect of work discipline on employee performance with the work environment as a moderating variable at PT SINERGI integra service using the Structural Equation Modeling (SEM) method - I Made Aryata; I Gede Marendra (Institute of Computer Science (IOCS), 2023)
PT SINERGI Integra Service is a cleaning contract service provider company that has been established since 2007 with its head office in Jakarta, one of the branches located in Tangerang Regency with a total of 150 employees. Based on Company data from 2019 to 2022 where the average employee performance achievement in 2021 is only 78.4% where this achievement has decreased by 2% compared to 2019. Based on the disciplinary data of PT SINERGI's employees which can be seen in the employee attendance data where there was an increase in the number of employee absence events in 2021 as many as 516 events where the value increased by 328.66% compared to 2019. On the other hand, the work environment also has an impact on employee performance. Based on research conducted by Irawan (2021), it shows that the work environment has a significant effect on the performance of civil servants at the Serpong District Office. ased on the results of research conducted using the Structural Equation Modeling Method, it was found that Work Discipline has an effect on Employee Performance with a p-value of 0.050 and the Work Environment has no effect on Employee Performance with a p-value of 0.330 and it can be concluded that the Work Environment as a moderating variable strengthens the influence of Work Discipline on Employee Performance with a p-value of 0.003.